Diversity in Computer Science Design Artefacts for Equity and Inclusion - Bjørn, Pernille; Menendez-Blanco, Maria; Borsotti, Valeria (Springer International Publishing : Imprint: Springer, 2023)
This is an open access book that covers the complete set of experiences and results of the FemTech.dk research which we have had conducted between 2016-2021 - from initiate idea to societal communication. Diversity in Computer Science: Design Artefacts for Equity and Inclusion presents and documents the principles, results, and learnings behind the research initiative FemTech.dk, which was created in 2016 and continues today as an important part of the Department of Computer Science at the University of Copenhagen's strategic development for years to come. FemTech.dk was created in 2016 to engage with research within gender and diversity and to explore the role of gender equity as part of digital technology design and development. FemTech.dk considers how and why computer science as a field and profession in Denmark has such a distinct unbalanced gender representation in the 21st century. This book is also the story of how we (the authors) as computer science researchers embarked on a journey to engage with a new research field - equity and gender in computing - about which we had only sporadic knowledge when we began. We refer here to equity and gender in computing as a research field - but in reality, this research field is a multiplicity of entangled paths, concepts, and directions that forms important and critical insights about society, gender, politics, and infrastructures which are published in different venues and often have very different sets of criteria, values, and assumptions. Thus, part of our journey is also to learn and engage with all these different streams of research, concepts, and theoretical approaches and, through these engagements, to identify and develop our own theoretical platform, which has a foundation in our research backgrounds in Human-Computer Interaction broadly - and Interaction Design & Computer Supported Cooperative Work specifically.